2016
DOI: 10.1037/qup0000044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring positive youth development among young people who leave school without graduating high school: A focus on social and emotional competencies.

Abstract: Much qualitative and quantitative research has examined the individual and contextual risk factors of youth who have left high school without graduating. However, few studies have examined their strengths and, to the authors' knowledge, no studies have used a positive youth development (PYD) perspective. To begin to fill this gap, we explored a component of the PYD process, an individual's social and emotional competencies, among 27 youth (57.64% male; 45% African American and 24% Hispanic) who had previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Specifically, researchers have hypothesized the potential role of emotional competence (i.e., emotional awareness, coping skills) in the utilization (Rickwood, Deane, Wilson, & Ciarrochi, ) and effectiveness (Gratz, Weiss, & Tull, ) of mental health services. Emotional competence refers to an individual's ability to identify, describe, understand, and manage emotions (Ciarrochi & Deane, ) and has been linked to enhanced decision‐making (e.g., Avsec, ), lower impulsivity (e.g., Checa & Fernández‐Berrocal, ), and better social and interpersonal functioning (e.g., Nelis et al, ; Zaff et al, ). Therefore, emotional competence may play a role in help‐seeking.…”
mentioning
confidence: 99%
“…Specifically, researchers have hypothesized the potential role of emotional competence (i.e., emotional awareness, coping skills) in the utilization (Rickwood, Deane, Wilson, & Ciarrochi, ) and effectiveness (Gratz, Weiss, & Tull, ) of mental health services. Emotional competence refers to an individual's ability to identify, describe, understand, and manage emotions (Ciarrochi & Deane, ) and has been linked to enhanced decision‐making (e.g., Avsec, ), lower impulsivity (e.g., Checa & Fernández‐Berrocal, ), and better social and interpersonal functioning (e.g., Nelis et al, ; Zaff et al, ). Therefore, emotional competence may play a role in help‐seeking.…”
mentioning
confidence: 99%
“…To them, they had lost education, which, Bridgeland et al (2006) argue, facilitates all-round life, yet they remained resilient as they made efforts to engage themselves with NGOs in various activities. To this end, Zaff et al (2014) concluded from a study on premature school exit prevention that students who left school prematurely had the strength to cope in hard contexts and were much more resilient than how current researches portray them or imply.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing from advances in brain science, Babcock argues that trauma-informed efforts need to consider how overactivity within the limbic system due to prolonged exposure to poverty, stress and trauma impacts development of the prefrontal cortex which is needed for establishing a future time perspective, setting goals and problem-solving. While Zaff and his colleagues advocate for a web of support to work with high need, high opportunity youth (Zaff et al, 2016), given the potential for emotional and mental health challenges, it is also important that programs provide access to counseling support, especially to help youth become ready consider future possibilities.…”
Section: Incorporate Trauma Informed Program Design Strategiesmentioning
confidence: 99%